Renewable Energy Transition Activism and Fighting Environmental Pollution - Wardana, Bagus Adi; Purwanto, Danang; Astutik, Dwi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The climate change agenda needs serious attention from every global society. Responsibility for human activities that have the potential for climate change is a shared responsibility. The solution to the problem of climate change can be traced to the roots of the problem. Environmental pollution is one of the causes of climate change problems. Handling environmental pollution can be done by transitioning from fossil energy to clean and renewable energy. The energy transition must be carried out as a whole by the whole society. This energy transition can be pursued through social movements. This study aims to analyze the activism of the Bersihkan Indonesia’s Coalition in efforts to fight against environmental pollution through renewable energy transition solutions. Based on research results, the activism of the Bersihkan Indonesia’s Coalition is a new social movement that aims to achieve a renewable energy transition. Activist activity in conveying the issue of the renewable energy transition through equal public space channels free of intervention. The Bersihkan Indonesia Movement proceeds in the political discourse of deliberative democracy. Equal citizen participation is part of the principle of inclusiveness in the renewable energy transition.